'Babylons': toponyms and symbolism of stone labyrinths in Arctic Russia. (2nd April 2016) - Mizin, V.
ABSTRACT: In Russian research in recent years there has been a revision of many ideas about the stone labyrinths on the coasts of the White and Barents Seas, especially regarding claims concerning the 'prehistoric' dating and the 'sacred' meaning of stone labyrinths. Against this background, the paper examines the previously little-studied issue of Pomorian names of stone labyrinths and the possible symbolism of stone labyrinths in northern Russia in the context of medieval culture.